Pathways, Histories, and ScreenDance Diaries: Sarah Elgart in Conversation - Elgart, Sarah; Bench, Harmony (The International Journal of Screendance, 2019)
An interview of Sarah Elgart by Harmony Bench, which took place via Skype on January 11, 2019.